1992
DOI: 10.2134/agronj1992.00021962008400040024x
|View full text |Cite
|
Sign up to set email alerts
|

Management and Dynamics of Potassium in a Humid Tropical Ultisol under a Rice‐Cowpea Rotation

Abstract: Little is known about the role of K fertilization, stover management, and tillage methods on soil K availability as they affect rice (Oryza sativa L.) and cowpea [Vigina unguiculata (L.) Walp.] productivity on Ultisols of the humid tropics. The effects of five K rates (0‐120 kg K ha−1), returning or removing stover, and three tillage methods (no‐till, strip, and conventional) were evaluated during 12 crops of rice and cowpea grown for a 4‐yr period. Fertilizer K was applied to the first seven crops. The site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…These consequences are to be expected considering the ample evidence in Table S4 (for the online version of the paper) that KCl inputs are often ineffective for increasing yield, but will be more serious when yield is depressed. The latter effect has indeed been observed, and was significant in field studies with corn 38,144,148,192 , soybean 120,125,131,175 , wheat (Triticum aestivum L.) 186 , sugarbeet (Beta vulgaris L.) 139 , sugarcane (Saccharum officinarum L.) 127 , alfalfa 145 , peanut (Arachis hypogaea L.) 109,191 , rape (Brassica napus L.) 176 and cowpea (Vigna unguiculata L.) 166 . In several of these studies, the loss of yield was intensified by increasing the rate of KCl application 38,109,120,125,175,192 , and in some cases the higher rate transformed significant yield gain to loss 127,186 .…”
Section: Fertilizer Value Of Potassium Chloridementioning
confidence: 79%
“…These consequences are to be expected considering the ample evidence in Table S4 (for the online version of the paper) that KCl inputs are often ineffective for increasing yield, but will be more serious when yield is depressed. The latter effect has indeed been observed, and was significant in field studies with corn 38,144,148,192 , soybean 120,125,131,175 , wheat (Triticum aestivum L.) 186 , sugarbeet (Beta vulgaris L.) 139 , sugarcane (Saccharum officinarum L.) 127 , alfalfa 145 , peanut (Arachis hypogaea L.) 109,191 , rape (Brassica napus L.) 176 and cowpea (Vigna unguiculata L.) 166 . In several of these studies, the loss of yield was intensified by increasing the rate of KCl application 38,109,120,125,175,192 , and in some cases the higher rate transformed significant yield gain to loss 127,186 .…”
Section: Fertilizer Value Of Potassium Chloridementioning
confidence: 79%
“…Research with flood-irrigated rice has shown weak or no significant correlation between relative rice yield or growth and soil-P availability indices from various STP methods (Chang, 1978;Khalid et al, 1979;Shahandeh et al, 1994Shahandeh et al, , 1995. Limited research suggests that STK is meaningful for rice grown under flooded soil conditions, with STK explaining 41 to 61% of the variability in relative rice yield (Cox and Uribe, 1992;. Arkansas research has shown that Mehlich-3 extractable P is not a good predictor of rice relative yield (r 2 = 0.17) response to P fertilization .…”
Section: Discussionmentioning
confidence: 99%
“…because of immobilization of native soil N) and FNR was usually not significantly reduced when residues and fertilizer were applied together (Table 6). Many studies have shown the positive residual effect of straw incorporation on the K fertility status of upland and lowland rice systems (Cox and Uribe 1992;Prasad et al 1999;Dierolf and Yost 2000). Rice straw contains approximately 80% of the above ground plant K and can amount to over 150 kg K ha -1 (Dobermann et al 1996Dobbermann and Fairhurst 2000).…”
Section: Yield Response To Organic Residues Alonementioning
confidence: 99%